The Matter in Extreme Conditions instrument at the Linac Coherent Light Source. (20th April 2015) - Nagler, Bob; Arnold, Brice; Bouchard, Gary; Boyce, Richard F.; Boyce, Richard M.; Callen, Alice; Campell, Marc; Curiel, Ruben; Galtier, Eric; Garofoli, Justin; Granados, Eduardo; Hastings, Jerry; et al.
<x xml:space="preserve">Abstract</x> The LCLS beam provides revolutionary capabilities for studying the transient behavior of matter in extreme conditions. The particular strength of the Matter in Extreme Conditions instrument is that it combines the unique LCLS beam with high‐power optical laser beams, and a suite of dedicated diagnostics tailored for this field of science. In this paper an overview of the beamline, the capabilities of the instrumentation, and selected highlights of experiments and commissioning results are presented.